The Use Of Three Dimensional Dice Media In Improving The Hijaiyah Letters Reading Ability Of Children Age 4-5 Years In TK Panti Puruhita Semarang - Solekha, Nazla Umami; Khamidun, Khamidun (Jurusan PGPAUD FIP UNNES, 2019)
The Al-Qur'an is the best way of life for human which is written in Arabic using hijaiyah letters. Al-Qur'an includes many functions that guide humans in living life. Because of the important role of the AL-Qur’an in human life, the command to teach the AL-Qur’an from an early age is contained in the words of Allah SWT and hadith. Al-Quran learning for young children begins by introducing hijaiyah letters as the composing letters of the AL-Qur’an. Three-dimensional dice media can be one of the media used in learning to read hijaiyah letters for early childhood. The problem examined in this study is whether the use of three-dimensional dice media can improve the ability to read hijaiyah letters of children aged 4-5 years in Panti Puruhita Kindergarten Semarang. This study aims to determine the increase in the ability to read hijaiyah letters of children aged 4-5 years through the use of three-dimensional dice media in kindergarten Panti Puruhita Semarang Kindergarten. This is experimental research, with one group pretest-posttest design research design. The population in this study is 30 students aged 4-5 years Panti Puruhita Kindergarten Semarang. The sampling technique uses purposive sampling. The sample is 30 students aged 4-5 years at the Panti Puruhita Kindergarten Semarang. Data collection methods use observation, documentation, and questionnaires. The questionnaire is used to measure the ability to read hijaiyah letters of children aged 4-5 years. The collected data is then analyzed by paired sample t-test using SPSS 21 for Windows. Based on calculations using paired sample t-test, the value of Sig. < 0.05 (0,000 < 0.05), and the tcount < ttable (-14,135 <1,697), so that the alternative hypothesis (Ha) can be accepted. The amount of increase that occurred in the ability to read hijaiyah letters of children aged 4-5 years in Semarang Panti Puruhita Kindergarten is 26.9 after being treated in the form of learning using three-dimensional dice media. The increase is obtained from the difference between the mean of pretest and posttest. Keywords: Hijaiyah Letters Reading Ability, Three Dimensional Dice Media, Children 4-5 Years